Is Economic Volatility Detrimental to Global Sustainability? - Huang, Yongfu (Oxford University Press on behalf of the World Bank, 2013)
In a dynamic panel data model allowing for error cross-section dependence, output volatility is found to impede sustainable development. Through a financial development channel (liquidity liability ratio), output volatility exerts a significant effect on depletion of natural resources, a key component of sustainability. Low-income countries, low energy-intensity countries, and low trade-share countries tend to be especially vulnerable to macroeconomic volatility and shocks. The findings highlight the interaction between global financial markets and the wider economy as a key factor influencing sustainable development, with important implications for macroeconomic and environmental policies in an integrated global green economy.